Effect of Different Parameters on Enzymatic Hydrolysis of Hazelnut Shells - Özcan Gezen; İrem Deniz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In the last few decades, the increasing levels of environmental pollution have prompted a shift towards alternative energy sources and biobased solutions, such as lignocellulosic biomass. Lignocellulosic biomass (LB) is primarily derived from plants and is composed mainly of polysaccharides, namely cellulose, hemicellulose, and the aromatic polymer lignin. Hazelnut shells (HS), with a high lignin content of 43%, hemicellulose of 30%, and cellulose of 26%, hold promise as a valuable source of LB. In order to process those LB, lignin and hemicellulose are separated using various treatment methods. However, instead of being used solely for combustion, lignin-containing materials can be valorized for a range of purposes, from biomedical applications to the energy sector. In this study, the enzymatic hydrolysis of HS was conducted over different time periods (24, 48, 72, and 96 hours), at different temperature values with varying enzyme concentrations (0.05, 0.1, and 0.25 mL of cellulase/xylanase enzyme cocktail). To enhance the enzymatic hydrolysis, an alkaline pretreatment method using sodium hydroxide (NaOH) was employed. The results demonstrate that the maximum sugar concentration was achieved at 50°C, after 72 hours, and with a cellulase/xylanase cocktail concentration of 0.1 mL.